Implikasi Kebebasan Pers Terhadap Dinamika Politik Islam di Sumatera Utara Pada Masa Reformasi Periode 1998-2011 - Nirwansyah Putra (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2017)
Post-reform  period,  press  is  not  facing  the  power  only,  but  also   capital-media   owner   and   professionalism   itself.   This impacted  political  Islam  dynamics  in  North  Sumatra,  directly or  indirectly.  Islamic  political  discourse  in  the  media  during 1998-2011   period,   inseparable   with   the   political   Islam depoliticization in the past as well as the power and economy pragmatism,  also  determines  the  general  islamic  discourse and  weakening  the  potential  political  power  of  Islam.  The absence  of  Islamic  political  media  and  structured-systematic special  programs  in  Islamic  journalism  and  the  existence  of  media that are generally common-secular segmented, causing the  agenda  and  the  political  Islam  discourse  depends  on owner  ideological  considerations,  market  segmentation  and policy of secular media.